Visible Light Driven Ultrasensitive and Selective NO2 Detection in Tin Oxide Nanoparticles with Sulfur Doping Assisted by l‐Cysteine. Issue 12 (20th January 2022) - Eom, Tae Hoon; Cho, Sung Hwan; Suh, Jun Min; Kim, Taehoon; Yang, Jin Wook; Lee, Tae Hyung; Jun, Sang Eon; Kim, Seung Ju; Lee, Jongwon; Hong, Seong‐Hyeon; Jang, Ho Won
Abstract: In the pandemic era, the development of high‐performance indoor air quality monitoring sensors has become more critical than ever. NO2 is one of the most toxic gases in daily life, which induces severe respiratory diseases. Thus, the real‐time monitoring of low concentrations of NO2 is highly required. Herein, a visible light‐driven ultrasensitive and selective chemoresistive NO2 sensor is presented based on sulfur‐doped SnO2 nanoparticles. Sulfur‐doped SnO2 nanoparticles are synthesized by incorporating l ‐cysteine as a sulfur doping agent, which also increases the surface area. The cationic and anionic doping of sulfur induces the formation of intermediate states in the band gap, highly contributing to the substantial enhancement of gas sensing performance under visible light illumination. Extraordinary gas sensing performances such as the gas response of 418 to 5 ppm of NO2 and a detection limit of 0.9 ppt are achieved under blue light illumination. Even under red light illumination, sulfur‐doped SnO2 nanoparticles exhibit stable gas sensing. The endurance to humidity and long‐term stability of the sensor are outstanding, which amplify the capability as an indoor air quality monitoring sensor. Overall, this study suggests an innovative strategy for developing the next generation of electronic noses. Abstract : A strategy for ultrasensitive and selective detection of NO2 based on S‐doped SnO2 nanoparticles by visible light illumination is suggested. Cationic and anionic sulfur doping improve the surface area and light absorption. The gas sensing performance at room temperature is significantly improved by S doping and visible light illumination.